Carbon Nanotubes: An All‐Solution‐Based Hybrid CMOS‐Like Quantum Dot/Carbon Nanotube Inverter (Adv. Mater. 35/2017). Issue 35 (September 2017) - Shulga, Artem G.; Derenskyi, Vladimir; Salazar‐Rios, Jorge Mario; Dirin, Dmitry N.; Fritsch, Martin; Kovalenko, Maksym V.; Scherf, Ullrich; Loi, Maria A.
Abstract : A hybrid voltage inverter is made with two field‐effect transistors, one using quantum dots as active material and the other polymer‐wrapped carbon nanotubes. In article number1701764, Maria A. Loi and co‐workers demonstrate that different solution‐processable, low‐dimensional materials can be combined to obtain high‐performance, low‐cost, and low‐voltage electronics.